Layering the introductory history of Europe course - Waddy, Helena (Teaching History: A Journal of Methods, 1997)
One of my students in the introductory "History of Europe since 1600" course recently entitled his paper "The Constitutional Relay Race." He was reacting to an image that I had developed to assist students in understanding the history of constitutional government in modern Europe. The British team started the relay race in the seventeenth century, passing the torch to their American colonist colleagues, who in turn handed the torch on to the French revolutionaries, who ran with it into the heart of Europe. Similarly, men started the race to full suffrage, passing the torch to women, who then handed it on to students in the late 1960s. With this image I try to illuminate the historical "flow" that we cover in the first "run-through" of our period. To energize my students’ understanding of the connections flowing from the beginnings in 1600 through to the state of European society today, I have structured the course into three of these separate but interrelated run throughs; each course section covers the entire period but with a different focus, and each culminates in a reiterative paper that retraces the analysis we have just pursued.